Chikungunya virus of Asian and Central/East African genotypes in Malaysia - Sam, I.C.; Chan, Y.F.; Chan, S.Y.; Loong, S.K.; Chin, H.K.; Hooi, P.S.; Ganeswrie, R.; AbuBakar, Sazaly (2009)
Background: Chikungunya virus (CHIKV) of the Central/East African genotype has caused large outbreaks worldwide in recent years. In Malaysia, limited CHIKV outbreaks of the endemic Asian and imported Central/East African genotypes were reported in 1998 and 2006. Since April 2008, an unprecedented nationwide outbreak has affected Malaysia. Objective: To study the molecular epidemiology of the current Malaysian CHIKV outbreak, and to evaluate cross-neutralisation activity of serum from infected patients against isolates of Asian and Central/East African genotypes. Study design: Serum samples were collected from 83 patients presenting in 2008, and tested with PCR for the El gene, virus isolation, and for IgM. Phylogenetic analysis was performed on partial El gene sequences of 837 bp length. Convalescent serum from the current outbreak and Bagan Panchor outbreak (Asian genotype, 2006) were tested for cross-neutralising activity against representative strains from each outbreak. Results: CHIKV was confirmed in 34 patients (41.0). The current outbreak strain has the A226V mutation in the El structural protein, and grouped with Central/East African isolates from recent global outbreaks. Serum cross-neutralisation activity against both Central/East African and Asian genotypes was observed at titres from 40 to 1280. Conclusions: The CHIKV strain causing the largest Malaysian outbreak is of the Central/East African genotype. The presence of the A226V mutation, which enhances transmissibility of CHIKV by Aedes albopictus, may explain the extensive spread especially in rural areas. Serum cross-neutralisation of different genotypes may aid potential vaccines and limit the effect of future outbreaks. (C) 2009 Elsevier B.V. All rights reserved.